Theoretical review on students’ oral participation in English classrooms - Tran , Hoa Mi (Journal of Technical Education Science, 2021)
This review summarizes the relevant research on students’ oral participation in classrooms where English is used as a means of instructions. Specifically, this library-based research reviews studies that have touched upon the merits of promoting students’ oral participation in class and factors influencing such activities. It has been found out that students’ classroom participation is highly correlated with their academic achievements and English proficiency. The review of literature indicates several aspects that can affect students’ engagement in oral activities in English classes. These factors include cognitive, pedagogical, affective, socio-cultural, and linguistic features. Finally, this review discusses gaps in the literature and directions that future studies may take to address these gaps. These implications include reconsidering the way of categorizing the factors, further examining the effects of teacher’s traits and socio-cultural factors on students’ classroom oral participation in the recent days, especially when Western values integrated more and more strongly to Asian nations.